PEMIKIRAN ABDULLAH NASHIH ULWAN TENTANG TANGGUNG JAWAB PENDIDIKAN MORAL PENDEKATAN FILSAFAT AKSIOLOGI - Zakiyah Nurul Hidayah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Recently, there have been many cases of violence and child crimes ranging from negotiation, persecution, theft, sexual harassment, and murder. The abnormal behavior that occurs among children even in the scope of education with juvenile perpetrators is an important note of the low level of morality of children today. The aim of this study is to describe the formula of moral education developed by Abdullah Nashih Ulwan through a philosophical approach to axiology. The method used is qualitative-descriptive, using library research. In this research, the researchers used the book Tarbiyyatul Aulad Fil Islam by Abdullah Nashih Ulwan as a source of research data and took sources from journals, articles, literature, and books related to research topics as a secondary source of data. Content analysis techniques are used by researchers to process data after the data required for the research has been collected. This research concluded that the moral education of Abdullah Nashih Ulwan should be based on the education of faith because faith education has a great influence on the attitude and character embedded in the child. While reviewed from the philosophical point of view of the axiology of the moral education of children, Abdullah Nashih Ulwan's perspective can provide positive values for the life of children from childhood to adulthood. For example, the values of goodness are shidiq (honesty), trust (reliability, consistency), itar (priority), helping those who need help, respecting parents, respect for neighbors and guests, and having a loving attitude toward each other. Keywords: Axiology, Abdullah Nashih Ulwan, Moral Education